Sistem Informasi E-Marketplace Penyedia Jasa Sewa Dekorasi Berbasis Website - Uchti Nur Rachmah; Chandra Kesuma; Sunanto - Universitas Bina Sarana Informatika (Indonesian Journal of Networking and Security (IJNS), 2021)
Abstract- Organizing an event organized by private or organizational is incomplete without any decoration as a living atmosphere. Decorations play an important role on various types of events such as weddings, engagements, birthday celebrations, and celebrations on the big day. There are many entrepreneurs engaged in the rental of decorations in the region of Purbalingga and Purwokerto. The obstacles that are often encountered by the rental service Finder at this time is a lack of information about the service provider decorating the rental so it is difficult to determine the choice of decoration that suits the desired criteria. Through E-Marketplace information System decorating rental service provider (The decors) based Website authors provide solutions to help service seekers to easily get pricing information from various service providers as well as can perform decorating rental transactions. The software development methods used by the authors on this research are agile methods. Keywords: Information systems, Decorating, Leasing, E-Marketplace, Decors. Abstrak - Penyelenggaraan sebuah acara yang diselenggarakan oleh pribadi maupun organisasi tidak lengkap tanpa adanya dekorasi sebagai penghidup suasana. Dekorasi memegang peran penting pada berbagai jenis acara seperti pernikahan, pertunangan, perayaan ulang tahun, hingga perayaan pada hari besar. Terdapat banyak pengusaha yang bergerak di bidang penyewaan dekorasi di wilayah Purbalingga dan Purwokerto. Kendala yang sering dijumpai oleh pencari jasa sewa dekorasi saat ini adalah kurangnya informasi tentang penyedia jasa sewa dekorasi sehingga sulit untuk menentukan pilihan dekorasi yang sesuai dengan kriteria yang diinginkan. Melalui Sistem Informasi E-Marketplace Penyedia Jasa Sewa Dekorasi (Pendekor) Berbasis Website penulis memberikan solusi untuk membantu pencari jasa agar mudah mendapatkan informasi harga dari berbagai penyedia jasa sekaligus dapat melakukan transaksi penyewaan dekorasi. Metode pengembangan perangkat lunak yang digunakan penulis pada penelitian ini adalah metode agile. Kata kunci : Sistem Informasi, Dekorasi, Penyewaan, E-Marketplace, Pendekor.